CRITICISM OF ELEMENTARY SCHOOL STUDENT LEARNING BOOKS IN THE LINGUISTIC THEORY STUDY - Halimatussakdiah Halimatussakdiah; Iis Suwartini; Febi Junaidi; Ramadhan Kusuma Yuda; Suryo Ediyono (Universitas Negeri Medan, 2019)
Abstract: Criticism Of Elementary School Student Learning Books In The Linguistic Theory Study. The distribution of textbooks, both printed and electronic, did not all obtain a recommendation on eligibility from the National Book Center. This paper is intended to provide criticism of the textbooks used in language learning. The analysis is done by studying the literature with the theory approach to linguistic schools. This is done to ensure that the developed textbooks do indeed contain the linguistic elements required by the curriculum. As for the book criticized